Buoyancy and Stability Analysis of Ark’a Modulam Amphibious Foundation Model - Nomeritae Nomeritae; Wijanarka Wijanarka; Rudi Waluyo (Journal of Infrastructure & Facility Asset Management, 2020)
To solve problems of settlement in floodplain areas, research on anti-flood foundation model is crucial. The anti-flood foundation model should be able to float during flood and to remain on land during non-flood conditions. This research focused on an amphibious foundation model named Ark’a Modulam. The reliability of Ark’a Modulam floating construction was analyzed for buoyancy and stability against vertical and horizontal loads. Two floating constructions were designed based on knock down and rigid systems. Both systems were designed using iron pipes with 2.5” and 4" of diameter. No significant differences were found in the buoyancy forces of the 2 floating construction systems. The load that can be supported by 1 floating construction was a maximum of 0.954 ton and stable at a floating depth limit of 43.2 cm. The stability of the floating construction should include the effect of vertical drive piles. The vertical and horizontal loads acting on the construction positioned inside Kahayan River during an extreme flood was also analyzed. During an extreme flood with 100 years of return period, the construction of one vertical drive piles should able to support vertical forces equal to or larger than 7.50 ton.